2004
DOI: 10.1002/da.20029
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural evaluation of the Panic Disorder Severity Scale in Japan

Abstract: The Panic Disorder Severity Scale (PDSS) [Shear et al., 1997] is rapidly gaining world-wide acceptance as a standard global severity measure of panic disorder, however, its cross-cultural validity and reliability have not been reported yet. We developed the Japanese version of the PDSS and examined its factor structure, internal consistency and inter-rater reliability and concurrent validity among Japanese patients with panic disorder with or without agoraphobia. We also established rules of thumb for interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 18 publications
(23 reference statements)
2
34
0
Order By: Relevance
“…Three of these reports [Kim, 2001;Monkul et al, 2004;Shear et al, 1997] concluded that the PDSS is most properly viewed as a two-factor measure, but the other two studies [Shear et al, 2001;Yamamoto et al, 2004] asserted that the single-factor model evidences better fit indices than did the two-factor model. Essentially, the results of both EFA and CFA have been discrepant.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Three of these reports [Kim, 2001;Monkul et al, 2004;Shear et al, 1997] concluded that the PDSS is most properly viewed as a two-factor measure, but the other two studies [Shear et al, 2001;Yamamoto et al, 2004] asserted that the single-factor model evidences better fit indices than did the two-factor model. Essentially, the results of both EFA and CFA have been discrepant.…”
Section: Introductionmentioning
confidence: 97%
“…Also, the psychometric properties of the non-English versions and the cross-cultural validity of the PDSS have been addressed in several studies [Kim, 2001;Monkul et al, 2004;Yamamoto et al, 2004]. In these studies, the PDSS evidenced adequate test-retest reliability, internal consistency, and good discriminant, concurrent, and criterion-related validities.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…15 This scale has sufficiently high reliability, with a Cronbach α of 0.86; a total score > 16 corresponds to severe panic disorder in the Japanese version. 16 Subjective sleep conditions were assessed using the self-rating Pittsburgh Sleep Quality Index (PSQI). 17 The PSQI is an effective instrument to evaluate subjective sleep disturbance by measuring 7 domains.…”
Section: Measurementsmentioning
confidence: 99%
“…ANOVA revealed significant differences among groups for the reduction rate in PDSS score DP, day panic group; DP/NP, day panic and nocturnal panic group; NP, nocturnal panic group. The dose equivalents of psychotropic drugs were calculated according to the report by Inagaki A et al 16 The doses of antidepressants are presented in mg basis of imipramine, and those of anxiolytics and hypnotics are presented in mg basis of diazepam. a vs DP, b vs NP, *p < 0.05, **p < 0.01.…”
Section: Medications and Treatment Responsementioning
confidence: 99%